Obtención de alimentos funcionales de Bactris gasipaes (pijuayo) - Aspajo Aspajo, Andrea Isabel (Universidad Nacional de la Amazonía Peruana, 2018)
Currently, the peach palm is highly sought after for having a fruit with a special flavor. The pulp of the peach palm when cooked is the most nutritious food of the fruits of the Amazon, since it has vitamin A, antioxidants, Omega 3 and Omega 6 as essential fatty acids as such. Most of the works tell us about the great benefits that it gives due to its great nutritional value that it contains as provitamin-A, vitamins such as A and E, antioxidants and essential fatty acids that can prevent many diseases in the future for people. In the present work, the research works that exist with the fruit of Bactris gasipaes will be reported to obtain functional foods and the benefits that the fruit offers us and also some productions that occur with the fruit of Bactris gasipaes; Development of a tortilla-type snack based on pijuayo fruit (Bactris gasipaes kunth), flour from the by-products of Bactris gasipaes hbk and its use in baking, preparation of fortified cookies with flour from Phaseolus vulgaris l (castilla bean) and Bactris gasipaes hbk (pijuayo) for human consumption.

Actualmente, el pijuayo es muy requerido por tener un fruto de sabor especial, La pulpa del pijuayo, en cocción, es el alimento más nutritivo proveniente de los frutos amazónicos, debido a la presencia de vitamina A, antioxidantes, Omega 3 y Omega 6 como ácidos grasos esenciales como tal. La mayoría de trabajos nos habla de los grandes beneficios que da por su gran valor nutricional que contiene como provitamina-A, vitaminas como A y E, antioxidantes y ácidos grasos esenciales que pueden prevenir muchas enfermedades a futuro a las personas. En el presente trabajo se dará a conocer los trabajos de investigación referentes al fruto de Bactris gasipaes para la obtención de los alimentos funcionales y otras propiedades beneficiosas que brinda el fruto; así como también algunos productos producidos en base al fruto del Bactris gasipaes: Desarrollo de un snack tipo tortilla a base de fruto de pijuayo (Bactris gasipaes kunth), harina de los subproductos de Bactris gasipaes HBK y su uso en panificación, producción de galletas fortificadas con harina de Phaseolus vulgaris l (frijol castilla) y Bactris gasipaes hbk (pijuayo) para el consumo humano.
Keywords: Alimentos funcionales; Pijuayo; Bactris gasipaes; Conceptos fundamentales; https://purl.org/pe-repo/ocde/ford#2.11.01